Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Magnetic properties of high grade Panxi ilmenite and Wide-Field magnetization Simulation: A Cross-Scale approach - Hanyu Lin; Dong Wang; Yinan Xie; Hongliang Shang; Zhicheng Hu; Jiangang Ku; Zhengchang Shen (Minerals Engineering, 2026)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

Structural assessment of post-impact concrete-filled steel tubular (CFST) members based on vibration tests and Bayesian model updating - Shang-Jun Chen; Chuan-Chuan Hou; Lin-Hai Han; Hua Yang (Engineering Structures, 2026)

Cover Image - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Long term deformation behavior of granite residual soil in the Greater Bay Area under three-dimensional cyclic stress paths - Zhaowei Shang; Lingwei Kong; Zhiao Gao; Huanwen Lin (Soil Dynamics and Earthquake Engineering, 2026)

Effect of Levilactobacillus brevis and Limosilactobacillus fermentum combined with carrot powder on the quality, safety, and microbial community of dry-fermented sausages - Siqi Zhang; Shimiao Wang; Xianhao Zhang; Hao Shang; Ying Yue; Bingrui Guo; Zhiping Zhao; Shengjie Li; Xinping Lin (Food Bioscience, 2026)

Safety evaluation and probiotic properties of Bacillus velezensis YK-19 capable of degrading deoxynivalenol: In vitro characterization and in vivo safety assessment in mice - Yukai Lin; Jingjing Zhao; Bo Wen; Songbiao Chen; Lei Wang; Xiaojing Xia; Yanzhao Xu; Yanyan Jia; Rongxian Guo; Ke Shang; Zuhua Yu; Chengshui Liao; et al. (Food Bioscience, 2026)

Corrigendum to “On the use of 6C seismic station for bending-to-shear and torsional building response assessment at TAIPEI 101” [Eng Struct 361 (2026) 122782] - Yara Rossi; Philippe Guéguen; Felix Bernauer; Kate Huihsuan Chen; Chin-Jen Lin; Chin-Shang Ku; Yaochieh Chen (Engineering Structures, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Key species reduces antibiotic resistance genes in food waste composting via enhanced cooperation potential and humification - Miaolian Hua; Shang Ding; Xiangwu Yao; Yuxiang Zhao; Lin Wang (Bioresource Technology, 2026)

S100 signaling in hair follicle biology: emerging mechanistic insights and therapeutic opportunities - Dongfan Wei; Hongwei Jia; Lin Shang; Di Zhang; Fenglin Zhuo (Journal of Molecular Histology, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Local protectionism in China’s government disclosure of food safety information - Jiangyuan Liang; Wen Lin; Shengping Shang; Jiehong Zhou (Food Policy, 2026)

Ternary synergistic activation of municipal waste incineration bottom ash for high-performance supplementary cementitious materials: Mechanisms, heavy metal immobilization, and sustainability - Jianwen Xiao; Hongxia Qiao; Minggang Shang; Lexiang Nie; Wenhao He; Feng Cao; Gangliang Lin (Environmental Research, 2026)

Exploring spatial and temporal variations in methane emissions from rice paddies - Shang-Hung Pao; Huey-Lin Lee; Chiao-Wen Lin; Wei-Jen Lin; Hsing-Juh Lin (European Journal of Agronomy, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Construction of low-pressure separation membranes with hierarchically porous structure via cross-linked cyclodextrin polymer modification for efficient dye/salt separation - Jing Yang; Xinyang Li; Zining Guo; Ligang Lin; Wensong Ma; Huiyang Shang; Yue Sun; Mengzhuo Zhang; Hao Wu; Qi Wang; Mengfan Hou; Hongchao Li (Chemical Engineering Journal, 2026)

The Lactate–lactylation circuitry in kidney fibrosis: cellular crosstalk from tubular metabolic reprogramming to macrophage effector functions - Yiwei Shang; Yunguang Wang; Qikai Luo; Ran He; Shaoting Wang; Binqi Wang; Weiye Lin; Yourou Zhou; Qing He; Qiang He; Juan Jin (Seminars in Immunopathology, 2026)

Streptomyces alfalfae XN-04 suppresses Fusarium crown rot by altering root exudation profiles and shaping rhizobacterial communities - Lifang Hu; Jing Chen; Ruimin Jia; Xiaomin Dong; Shang Cao; Lin Tian; Dongfang Ma; Yang Wang (Pesticide Biochemistry and Physiology, 2026)

Flexible MOF nanosheet based membranes for high-flux antifouling oil/water separation and reverse cross-flow cleaning - Ting Gong; Jizheng Shang; Hongyuan Zhu; Yifan Liu; Hang Jiang; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Journal of Hazardous Materials, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Optimization of drip irrigation strategies for major crops in salinized soil based on a two-dimensional agro-hydrological model - Zunqiu Xu; Yihui Xiong; Shuai Chen; Lin Wang; Songhao Shang (Field Crops Research, 2026)

On the use of 6C seismic station for bending-to-shear and torsional building response assessment at TAIPEI101 - Yara Rossi; Philippe Guéguen; Felix Bernauer; Kate Huihsuan Chen; Chin-Jen Lin; Chin-Shang Ku; Yaochieh Chen (Engineering Structures, 2026)

Isolation and Identification of Erysipelothrix sp. in Hybrid Grouper ( Epinephelus fuscoguttatus × E. lanceolatus ) in Taiwan - Shang‐Ting Wu; Yu‐Siang Lin; Chia‐Yu Hsieh (Journal of Fish Diseases, 2026)
In February 2025, a mortality event of unknown aetiology occurred at a hybrid grouper ( Epinephelus fuscoguttatus × Epinephelus lanceolatus ) aquaculture farm in southern Taiwan, with sporadic daily deaths persisting for a month. Four moribund groupers were collected over three sampling intervals for diagnostic investigation. Gross pathology revealed opaque white discoloration with multifocal petechial haemorrhages in the lateral musculature. Gram‐stained muscular viscous fluid smears showed abundant Gram‐positive, filamentous bacilli (2–100 μm in length). Histopathology of the skeletal muscle confirmed extensive Zenker's necrosis, with dense bacterial aggregates infiltrating necrotic myofibres. On blood agar at 28°C, smooth, greyish, α‐haemolytic colonies developed within 16–24 h; growth was restricted at 32°C and absent at 35°C. Full‐length 16S rRNA gene sequencing identified the isolates as Erysipelothrix . High‐resolution gyrB ‐based phylogenetic analysis clustered the isolates nearly identically with the dolphin‐derived E. rhusiopathiae strain KC‐Sb‐R1 (CP033601), distinct from swine‐derived E. rhusiopathiae (97.0%), E. piscisicarius (91.2%) and E. tonsillarum (83.9%). The isolates belonged to spa type B. To our knowledge, this is the first documented case of an E. rhusiopathiae ‐like infection causing myositis and intramuscular abscesses in grouper aquaculture, highlighting a potentially marine‐associated lineage with significant implications for aquatic veterinary medicine and public health.

Hydrothermal zircon recording multi-stage tectonic reworking in Permian volcaniclastic rocks of the Emeishan Large Igneous Province, Southwest China - Junlang Chen; Xiaohong Liu; Tong Lin; Mingyou Feng; Hongming Tang; Jie Tan; Weiwei Wang; Junxin Shang; Tenglong Hu; Yili Zhao (Mineralogy and Petrology, 2026)

VdbHLH60-VdMYB55-VdF3'5'H module positively regulates anthocyanin biosynthesis in rabbiteye blueberry (Vaccinium ashei) fruits - Lin Deng; Luonan Shen; Kui Zhou; Chunqiong Shang; Sulin Wen; Yi Min; Yuxin Leng; Xiaopeng Wen (Plant Science, 2026)

Revisiting zircon-melt REE partitioning systematics: new insight into shallow crustal melting on early Earth - Sheng Shang; Haoxiong He; Wim van Westrenen; Fraukje M. Brouwer; Yanhao Lin (Geochimica et Cosmochimica Acta, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Unveiling mechanistic insights of inactivated Aspergillus niger spore by fishery-waste-derived chitosan via synchrotron radiation tomography - Ying-Chen Chen; Chih-Huang Weng; Chun-Chieh Wang; Zi-Jing Lin; Shang-Ming Huang; Girma Sisay Wolde; Jenn-Wen Huang; Mo Da-Sang Hua; Yao-Tung Lin (Carbohydrate Polymers, 2026)

Impact of biochar particle size and content on small strain stiffness characteristics of amended expansive clay - Zhiao Gao; Lingwei Kong; Yong Wang; Hui Qin; Zhaowei Shang; Huanwen Lin; Yuan Zhou (Journal of Mountain Science, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Osteopontin as an emerging multifunctional food ingredient: recent advancements, production, applications, and challenges - Shiyu Lin; Xiuxiu Teng; Xinjie Shang; Shu Li; Jingjing Xu; Yao Tang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2026)

Genomic and Phenotypic Characterization of the Probiotic Potential and Safety of Bacillus velezensis CH3-2 Isolated from Chahua Chicken - Le Xu; Shang Wang; Shiyu Chen; Chen Liu; Haiyue Wu; Qinghua Liu; Minjie Hu; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Synergistic activation of lithium slag using solid-waste-derived alkali and sodium sulfate: Towards high-performance low-carbon cementitious materials - Yannian Zhang; Lin Zhang; Qingjie Wang; Moncef L. Nehdi; Zhijun Li; Baoyuan Wang; Yunzhi Shang; Xinyu Dong (Sustainable Chemistry and Pharmacy, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Transition from galloping to suppression in flow-induced vibration of a circular cylinder with a flexible plate at subcritical Reynolds numbers - Yuankun Sun; Jiasong Wang; Shuqing Wang; Junfeng Du; Xiancang Song; Ke Lin; Chao Shang (Ocean Engineering, 2026)

Constructed wetland assessment using BC-CaCO3/TiO2 biochar in acid mine drainage treatment: Performance and metagenomic insights - Thembeka Mabaso; Shang-Lien Lo; Hsiang-Yu Yang; Nai-Chun Lin (Journal of Environmental Chemical Engineering, 2026)

Assessing the reliability of isoGDGTs lake-level proxies across Tibetan Plateau and Central Asian lakes - Jiahan Shang; Lin Chen; Shilong Guo; Mengjing Li; Zhongwei Shen; Aifeng Zhou (Global and Planetary Change, 2026)

Compositional profiling and inter-cultivar variation of flavonoids in some red table grapes cultivated in China: Assessing the quality-indicative potential of anthocyanins, flavonols, and flavanols - Shang-Lin Wang; Hai-Bei Yan; Lin Wang; Xing-Chi Chen; Jun Wang; Fei He (Food Chemistry, 2026)

Film matrix modification synergize with active ingredient introduction strategy to synthesize polysaccharide-based active packaging with enhanced barrier performance and functional activity for efficient perishable fruit preservation - Zitian Liu; Ligang Lin; Jiaxin Zhang; Kui Niu; Minglun Cheng; Yuxuan Zhu; Bin Du; Wenlong Hou; Huiyang Shang (Food Hydrocolloids, 2026)

Switchable thermo-triggered and 3D-printable soy protein soft emulsion gels as fat analogs for plant-based meat - Ge Qiao; Xiao-Wei Chen; Xiao-Yang Luo; Lin-Shang Zhang; Xiao Liu (Food Hydrocolloids, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Solvent-induced structural transformation and dynamic luminescence modulation in hybrid Sb-based chlorides for multi-level encryption - Liqing Wang; Xingjun Li; Sizhe Liu; Wei Zhang; Xiaoli Luo; Xiaobo Gu; Guoyu Tang; Yao Lin; Xiaoying Shang; Shan Lu; Xueyuan Chen (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Linking dissolved organic matter sources to greenhouse gas potential in thermokarst lakes of the Qinghai–Tibet Plateau - Wenyan Liu; Zeyong Gao; Chengming Zhang; Fujun Niu; Yibo Wang; Zhanju Lin; Youhua Ran; Jing Luo; Guoan Yin; Yunhu Shang (Cold Regions Science and Technology, 2026)

Comparison of Morphological and Physical Parameters of Rain Cells Observed by FY-3G PMR and GPM DPR in Boreal Summer - Zhenhao Wu; Yunfei Fu; Peng Zhang; Songyan Gu; Jian Shang; Lin Chen (Journal of Meteorological Research, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

In Situ Hybridization and RT ‐ PCR Detection of Nervous Necrosis Virus in Fourfinger Threadfin, Eleutheronema tetradactylum , in Taiwan - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)
Between April and July 2020, suspected outbreaks of nervous necrosis virus (NNV) infection were observed in fourfinger threadfin ( Eleutheronema tetradactylum ) fingerling hatcheries in Pingtung County, southern Taiwan. Affected fish exhibited spiral swimming behaviour and abdominal distension, resulting in mortality rates between 50% and 100%. Histopathological examination showed severe vacuolation in the brain and ocular tissues, with large oval and/or irregular basophilic cytoplasmic inclusion bodies in the brain. Phylogenetic analysis of the viral replicase (RNA1) and capsid protein (RNA2) genes revealed high nucleotide sequence identities among the isolates in this study, with sequence similarity rates of 96.9%–99% for RNA1 and 98.2%–99.0% for RNA2 compared to RGNNV reference strains available in the NCBI GenBank database. This is the first detection of betanodavirus in fourfinger threadfin in Taiwan, using RT‐PCR and ISH. A positive correlation between elevated water temperatures and disease severity indicates the need for year‐round surveillance and genomic analysis to clarify the epidemiology of FTNNV. The data suggest that infected eggs may facilitate the vertical transmission of Betanodavirus. Crucially, utilising virus‐free broodstock, alongside routine health screening and environmental control, is essential for mitigating NNV risks in fourfinger threadfin aquaculture.

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

The climate effects of ultrafine particles: uncertainties and future perspectives - Yuzhi Jin; Jiandong Wang; Shang Wu; Zhouyang Zhang; Jiaping Wang; Zeyuan Tian; Bin Wang; Qihao Lin; Jing Cai; Chenxi Li; Lei Yao; Chao Liu; et al. (ENGINEERING Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Metabolomics reveals GABA as a key mediator of salinity stress in razor clam - Geqi Gao; Zihan Lin; Yuting Han; Mengwei Shang; Jiahui Sun; Donghong Niu; Jiale Li (Aquaculture, 2026)

WaveCastNet-C: Forecasting the significant wave height in the China Sea with a fully convolutional neural network - Hao Dai; Zhihan Xie; Famei Lei; Xining Zhang; Guomei Wei; Rui Lin; Weijie Zhang; Shaoping Shang (Ocean Engineering, 2026)

Insight into the transformation and influence of soil dissolved organic matter on pollutant degradation by microwave activated peroxymonosulfate - Xiao Shang; Xiwang Zhao; Xitao Liu; Xiaoyu Ma; Chunye Lin; Mengchang He; Wei Ouyang (Journal of Environmental Chemical Engineering, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Antioxidant and anti-aging activities of Salvia miltiorrhiza Bunge callus extracts in H2O2-induced premature senescence and chronological aging models of human dermal fibroblasts - Shinn-Zong Lin; Tzu-Kai Lin; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Yueh-Min Lin; Tsung-Jung Ho; Shang-Chuan Ng; Chih-Yang Huang (Biogerontology, 2026)

Cottonseed protein as a sustainable alternative plant protein: Basic characteristics, recent advancements, applications and limitations - Xinjie Shang; Shu Li; Shiyu Lin; Shihao Sun; Li Liang; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

Effect of slurry velocity on particle–fluid interaction in high gradient magnetic field - Hanyu Lin; Yinan Xie; Qian Wang; Hongliang Shang; Jiangang Ku; Zhengchang Shen (Minerals Engineering, 2026)

Construct dichlorine monoxide equilibrium at high chloride concentrations to reveal its overlooked reactivity and unique site-selectivity in degrading micropollutants - Chuanjing Lin; Binghua Jing; Yixiao Duan; Zexuan Ma; Lulu Li; Zhimin Ao; Chii Shang; Li Ling (Journal of Hazardous Materials, 2026)

Low-carbon cementitious materials from industrial wastes: synergistic sulfate-alkali activation of granulated blast furnace slag and lithium slag - Yannian Zhang; Lin Zhang; Qingjie Wang; Tao Gao; Weifeng Zhang; Yunzhi Shang; Zhijun Li (Waste Disposal & Sustainable Energy, 2026)

Identification of a novel stripe rust resistance locus in a Chinese wheat landrace by bulked segregant analysis of recombinant inbred lines combined with the 660 K SNP array - Liuyang Shang; Suyu Li; Yuqin Li; Fang Wang; Shutao Chen; Kanghui Zeng; Yanling Hu; Yinghui Li; Zhenzhen Wei; Lianquan Zhang; Guoyue Chen; Bihua Wu; et al. (Euphytica, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Complex variable solution for multi-step shallow tunnel excavation considering gravitational effects - Luo-bin Lin; Fu-quan Chen; Chang-jie Zheng; Shang-shun Lin (Tunnelling and Underground Space Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hidden heat at curbs: Using deep learning to map pedestrian-scale heat from air-conditioner exhaust and spatial inequity in Jiande, China - Ruiheng Li; Ziqi Shang; Ziqun Lin; Zhen Xu (Building and Environment, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Human umbilical cord MSC-derived exosomes attenuate radiation-induced pulmonary fibrosis via remodeling the gut-lung axis in mice - Yan Zhou; Haonan Wang; Ling Guo; Xiaodie Liu; Xing Wang; Yue Liu; Mengjuan Shang; Bo Zheng; Kewei Li; Lin Liu; Jing Li; Guirong Ding (Life Sciences in Space Research, 2026)

Multifunctional chitosan/polyvinyl alcohol film enhanced with N-TiO2 and jaboticaba peel extract for shrimp freshness monitoring and banana preservation - Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Shang-Ming Huang; Jenn-Wen Huang; Chanat Chokejaroenrat; Dong-Hau Kuo; Yao-Tung Lin (Food Packaging and Shelf Life, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Ag/AgCl@NH2-MIL-88B functionalized pH-responsive aerogel for enhanced organic pollutant removal via adsorption and photo-Fenton-like degradation synergy - Anrong Yao; Yafang Wang; Kai Wang; Haoyi Hu; Siyao Tian; Yeqian Ge; Lin Yang; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Journal of Environmental Chemical Engineering, 2025)

Harvesting low−grade heat by architecting the hierarchical porous structure of green delignified corn husk for solar−driven seawater desalination - Saqib Mehmood; Wang Jianquan; Jinlong Jiang; Chengwei Lin; Yanlong Shang; Du Ran (Journal of Environmental Chemical Engineering, 2025)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

A computationally driven screening-construction-mechanism strategy of magnetic molecularly imprinted polymers for aliphatic aldehydes detection - Yongqing Zhang; Xiaolong Shang; Jiaqi Guo; Ling Ao; Caihong Shen; Miao Liu; Feng Lin; Wenxian Li; Liqiang Zhang; Baoguo Sun; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Biocatalytic synthesis of margarine fat with zero-trans and low saturated fatty acids by Pichia pastoris lipase immobilized on resin - Xiao-Ya Guan; Jing Zhang; Xiao-Wei Chen; Lin-Shang Zhang; Shang-De Sun (Food Chemistry, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Forecasting intraday particle number size distribution: a functional time-series approach - Han Lin Shang; Israel Martinez Hernandez (Environmental and Ecological Statistics, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Erianin reverses 5-FU resistance by targeting CALM1/CAMKK2 and activating autophagy in colorectal cancer - Fangyuan Zhou; Luorui Shang; Jinxiao Li; Mengqi Zhang; Shuhan Wang; Yuju Cai; Qifeng Lin; Haiyang Gao; Shenglan Yang (Chemico-Biological Interactions, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Activation of ERK/MAPK signaling by MAZ through transcriptional repression of PPP3CA to promote osteoclastogenesis and osteoporosis progression: Functions and mechanisms - Xinying Shang; Wei Hu; Lin Zhang; Rui Wei (Tissue and Cell, 2025)

The impact of port investment along the 21st Century Maritime Silk Road on regional port network connectivity and its imbalance - Weishan Lin; Ling Sun; Tianshi Wang; Hui Shang; Wei Xu (Regional Studies in Marine Science, 2025)

Dissolved organic matter-mediated photosensitized activation of peracetic acid for micropollutant abatement in wastewater effluent - Hailin Wen; Chuanjing Lin; Chii Shang; Senhao Lu; Zijun Dong; Jingyun Fang; Ran Yin (Journal of Hazardous Materials, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Examining practical application feasibility of bismuth-embedded mesoporous silicon for effective removal of radioactive iodine - Ming Shang; Bin Wang; Jian Liu; Lin Zhu; Baoliang Xu; Tao Duan; Jing Chen (Chemical Engineering Journal, 2025)

A strategy for enhancing mechanical properties of electrically controlled solid propellant via in-situ-induced microphase separation - Huimin Nai; Qiyang Wang; Yingxue Ju; Yangshun Ren; Jiahui Li; Jizeng Shang; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Ceramifiable flame-retardant silicone rubber foam for long-term fire resistance and thermal insulating - Tao Lin; Ke Shang; Gui-De Lin; Jun-Sheng Wang; Jin-Jun Yang (Chemical Engineering Journal, 2025)

Radial artery intima-media thickening is a sensitive marker of atherosclerosis and coronary artery stenosis, a lesson from a 6-year study of a spontaneous monkey model - Jue Wang; Wen Zheng; Haibao Shang; Lin Pan; Ye Yuan; Wenli Chen; Chunguang Guo; Shihan Li; Xueting Sun; Jing Guo; Xiuqin Zhang (Molecular and Cellular Biochemistry, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Quantifying mutual transport contributions of ozone and its precursors among adjacent county-level cities during typical pollution episodes - Demian Lai; Yifei Chen; Yangjun Wang; Yan Zhang; Lin Xu; Zijia Ma; Burcak Kaynak; Shikang Tao; Yu Shang; Li Li (Urban Climate, 2025)

Tracing disinfection byproducts during shock chlorination of a seawater reverse osmosis (RO) desalination pilot and the blended and chlorinated potable water produced - Thi Xuan Hoa Le; Yingying Xiang; Chii Shang; Chuanjing Lin; Kun Wang (Desalination, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

Petrography, geochemistry, and zircon U–Pb chronology of the Late Ordovician metavolcanic suites in the eastern North Qilian orogenic belt, NW China: constraints on their petrogenesis and tectonic implications - Irshad Hussain; Zuochen Li; Xianzhi Pei; Lei Pei; Feng Gao; Mao Wang; Xiao Wang; Hao Lin; Li Qin; Shang Ji (Acta Geochimica, 2025)

The methods for the retrieval of land surface temperature in central Shijiazhuang using ASTER data - Biao Zeng; Guo-fei Shang; Xia Zhang; Ye-lin Shen; Yu-jia Tian; Zheng-hong Yan (Environmental Monitoring and Assessment, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Extraction, purification and antioxidant activity of Chlorella polysaccharide - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Changhua Shang (Algal Research, 2025)

Effects of DpWRI1-like gene overexpression in transgenic Dunaliella parva - Lingru Ruan; Juying Lin; Lina Wu; Yanyan Liang; Xiumin Zhang; Shiyu Liang; Limei Huang; Changhua Shang (Antonie van Leeuwenhoek, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Extreme degradation of alpine wet meadow decelerates soil heat transfer by preserving soil organic matter on the Qinghai–Tibet Plateau - Zeyong Gao; Chengming Zhang; Wengyan Liu; Fujun Niu; Yibo Wang; Zhanju Lin; Guoan Yin; Zekun Ding; Yunhu Shang; Jing Luo (Journal of Hydrology, 2025)

Letter to the editor: Comments on “Microplastic polyethylene induced inner ear dysfunction in murine model” - Haonan Lin; Liming Shang; Lexin Wang; Ke Xu (Journal of Hazardous Materials, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Corrigendum to “Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents” [Food Packaging and Shelf Life 46 (2024) 101361] - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Strategic carbon source supplementation enhances nitrite degradation by Pantoea sp. A5 in variable temperature conditions - Tzu-Yuan Sung; Anil Kumar Patel; Shang-Ru Lin; Chuan-Ting Huang; Ying-Tang Huang (Bioresource Technology, 2025)

Microwave-assisted green synthesis of 5-HMF from date seeds using solid-acid catalyst and ionic liquid - Subham Halder; Shang-Cyuan Chen; Chien-Hua Hsiao; Feng-Chih Chou; Yuan-Chung Lin (Biomass and Bioenergy, 2025)

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The tight-coupled SLAM system based on LiDAR and improved VGICP method for waterfront environments - Xun Chen; Yuanguang Lin; Xiaofei Yang; Shang Zhao (Ocean Engineering, 2025)

A comprehensive review of salt rejection and mitigation strategies in solar interfacial evaporation systems - Shang Liu; Qijun Yang; Shiteng Li; Meng Lin (Desalination, 2025)

Nanoengineered cellulose for sustainable selective separation of precious metals from electronic waste - Roya Koshani; Shang-Lin Yeh; Mica L. Pitcher; Lucas Lawrence Franz; Mitchell Robert Davis; Min Ju Park; Said Khalifa Ahmed Al Qassabi; Joelson Patricio Manuel Alves; Younes Shekarian; Hevapathiranage Chandima Sudantha Subasinghe; Sarma V. Pisupati; Mohammad Rezaee; et al. (Chemical Engineering Journal, 2025)

Novel Perspectives Focused on the Relationship Between Herpesvirus Encephalitis and Anti-GFAP-Antibody-Positive Astrocytopathy - Yuqiao Liao; Linxin Wen; Ruoyi Zheng; Yinan Shen; Teng-Ai Ha; Mingkai Lin; Ruogu Cheng; Ye Gao; Pei Shang (Molecular Neurobiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

The electrochemical degradation of enrofloxacin using RuO2-IrO2-TiO2/Ti electrodes: Kinetics, mechanism, and model prediction - Juxiang Chen; HongMei Yang; Yuxia Feng; Lin Liu; YuQiong Gao; Xinrong Shang (Journal of Water Process Engineering, 2025)

A peer-to-peer energy bidding and transaction framework for prosumers based on blockchain consensus mechanism and smart contract - Yi Shang; Xiaolan Li; Tianqi Xu; Lin Cui (Energy and Buildings, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Mutation Screening of ATXN1, ATXN2, and ATXN3 in Amyotrophic Lateral Sclerosis - Tianmi Yang; Qianqian Wei; Dejiang Pang; Yangfan Cheng; Jingxuan Huang; Junyu Lin; Yi Xiao; Qirui Jiang; Shichan Wang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Frost heave evaluation and prediction of high-speed railway subgrade with coarse filler in high altitude seasonal frozen region, northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Xingwen Fan; Minghao Liu; Chunqing Li; Yunhu Shang (Transportation Geotechnics, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Microbial diversity and antibacterial mechanism of slightly acidic electrolyzed water against Pseudomonas fluorescens in razor clam during storage - Xiaoting Xuan; Ziyi Zhang; Haitao Shang; Zheliang Sheng; Yan Cui; Xudong Lin; Shanqiao Chen; Lin Zhu (Food Research International, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Effectiveness of Conditioning Strategies in Improving Fish Fitness‐Related Traits - Zonghang Zhang; Guihui Ning; Fei Tong; Wuhan Lin; Yangke Shang; Daomin Peng; Wenhua Liu (Fish and Fisheries, 2025)
Although conditioning strategies are widely used to increase fish post‐release adaptability in stock enhancement projects, their effectiveness has not been systematically evaluated. Using a global‐scale meta‐analysis, we demonstrate that three major conditioning strategies, including environmental enrichment, life skills training and release tactic, can significantly improve fish fitness‐related traits, with the fitness indicator and developmental stage being the most important moderators for interpreting the high heterogeneity among cases. The effect size of approximate fitness indicators was marginally lower than that of post‐release behavioural traits. Our findings indicate the necessity of conditioning procedures and highlight the need to enact context‐dependent strategies in practical conservation projects.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Vitamin C encapsulated biomimetic nanogels with macrophage membrane decoration for chronic wound healing - Xin Yang; Xiang Lin; Jinbo Li; Tapani Viitala; Yuanjin Zhao; Hongbo Zhang; Luoran Shang (Chemical Engineering Journal, 2025)

Effects of rosmarinic acid covalent conjugation on the allergenicity and functional properties of egg white protein - Xuanpei Wang; Hao-Long Zeng; Jieli Shang; Yijie Chen; Lin Xu; Jine Wu; Zhiyong Gong; Xin Liu; Qing Yang (Food Hydrocolloids, 2025)

Enhancing pollution management in watersheds: A critical review of total maximum daily load (TMDL) implementation - Hantao Wang; Yijia Guan; Min Hu; Zhiqiang Hou; Yang Ping; Zhenzhou Zhang; Qingtao Zhang; Fangze Shang; Kairong Lin; Cuijie Feng (Environmental Research, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Extraction, purification and characterization of Spirulina phycocyanin - Juying Lin; Yan Pang; Yu Huo; Jiaming Jiang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

The dynamic adjusted system of sea use fees: An empirical research on the sea use management in Zhejiang province - Guanqiong Ye; Zeben Lian; Chong Chen; Chunyu Lin; Zhiguo He; Weidong Shang; Yongchao Zheng (Regional Studies in Marine Science, 2024)

Methods for detecting green tide in the Yellow Sea using Google Earth Engine platform - Yuhao Shang; Lingling Jiang; Lin Wang; Zixu Ye; Siwen Gao; Xiaohui Tang (Regional Studies in Marine Science, 2024)

Can big data policy drive urban carbon unlocking efficiency? A new approach based on double machine learning - Neng Shen; Guoping Zhang; Jingwen Zhou; Lin Zhang; Lianjun Wu; Jing Zhang; Xiaofei Shang (Journal of Environmental Management, 2024)

Analysis, accumulation, transformation, and impact of metallic nanoparticles in plants - Wenhua Li; Yan Tan; Guanjia Shang; Liqun Chen; Zhibin Wu; Yiqing Lin; Lin Luo; Yuan Yang (Journal of Environmental Chemical Engineering, 2024)

Phenolic compounds in dietary target the regulation of gut microbiota: Role in health and disease - Qinqiu Zhang; Yi Xu; Danka Bukvicki; Yue Peng; Fan Li; Qing Zhang; Jing Yan; Shang Lin; Shuxiang Liu; Wen Qin (Food Bioscience, 2024)

Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2024)

Engineering a shellfish-inspired bio-based double-layered smart packaging material with enhanced water resistance and barrier performance for universally applicable meat freshness monitoring - Zitian Liu; Qiying Wang; Ligang Lin; Qingrun Liu; Wensong Ma; Qi Cheng; Jing Yang; Fengling Tang; Meina Xu; Xu Yang; Huiyang Shang; Hao Wu (Chemical Engineering Journal, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Inhibitory effect of rosmarinic acid on IgE-trigged mast cell degranulation in vitro and in vivo - Binmei Jia; Hao-Long Zeng; Jieli Shang; Xuanpei Wang; Lin Xu; Min Fang; Fengbo Zeng; Qing Yang (Molecular Biology Reports, 2024)

Precise diagnosis of a hereditary spherocytosis patient with complicated hematological phenotype - Guanxia Liang; Zezhang Lin; Yang Zhang; Qianqian Zhang; Dina Zhu; Xiongda Liang; Hongting Xie; Xiaofeng Wei; Xuan Shang (Molecular Genetics and Genomics, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Targeting bacterial phospholipids and their synthesis pathways for antibiotic discovery - Meirong Song; Shang Chen; Wenhan Lin; Kui Zhu (Progress in Lipid Research, 2024)

Effect of plant species on wastewater treatment performance of a subsurface vertical-flow constructed wetland with step-feeding at low temperature - Menglu Huang; Lin Zhao; Zhen Wang; Ximing Sun; Qiongqiong Shang; Yihan Li; Mengxiao Li; Hongzhi Geng; Siyu Hu; Yongkui Yang (Journal of Environmental Management, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Stepwise reinforcement strategy for guar gum/sodium alginate based films: Introduction of carboxylated cellulose nanofibers by different methods and further calcium ion crosslinking - Zitian Liu; Qingrun Liu; Ligang Lin; Qiying Wang; Wensong Ma; Qi Cheng; Jing Yang; Fengling Tang; Meina Xu; Xu Yang; Huiyang Shang; Hao Wu (Food Hydrocolloids, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Fabrication of Fe-Ti heteroatom-based metal-organic framework with vantage defects for high-efficient arsenic removal from water - Shanshan Shang; Xinyu Chen; Chao Yang; Ying Zhou; Kaimin Shih; Lin Lin; Xiao-yan Li (Chemical Engineering Journal, 2024)

Streptococcus mitis enhances metal-induced apoptosis in reconstructed human gingiva but not skin - Yan Zhang; Lin Shang; Sanne Roffel; Sander W. Spiekstra; Dongmei Deng; Susan Gibbs (Toxicology in Vitro, 2024)

Roles of soil minerals in the degradation of chlorpyrifos and its intermediate by microwave activated peroxymonosulfate - Xiao Shang; Xitao Liu; Xiaoyu Ma; Wenbo Ren; Chunye Lin; Mengchang He; Wei Ouyang (Science of The Total Environment, 2024)

Molecular mechanism of saturated aldehyde oxidation: A DFT insight into volatiles forming from decanal thermal oxidation - Binchen Wang; Shaohua Dou; Shang Wang; Yi Wang; Sufang Zhang; Xinping Lin; Chaofan Ji; Liang Dong (Food Chemistry, 2024)

Strong absorption of silica over full solar spectrum boosted by interfacial junctions and light–heat–storage of Mg(OH)2–(CrOx–SiO2) - Rui-Min Hao; Lin Zhu; Teng-Fei Shang; Zhi-Bin Xu; Qin-Pei Wu (Chemical Engineering Journal, 2024)

In-situ surface reconstruction of CsPbl3 perovskite for efficient and stable solar cells - Weideren Dai; Yanzhuo Gou; Huili Wei; Chang Chen; Zexun Pan; Xu zhang; Liangyou Lin; Minghui Shang; Qunchao zhang; Xianbao Wang; Qidong Tai; Jinhua Li (Chemical Engineering Journal, 2024)

Assessing Normalized Difference Vegetation Index as a proxy of urban greenspace exposure - Yang Ju; Iryna Dronova; Qin Ma; Jian Lin; Mika R. Moran; Nelson Gouveia; Hong Hu; Haiwei Yin; Huiyan Shang (Urban Forestry & Urban Greening, 2024)

Cumulative frost heave and hydrothermal process of the high-speed railway subgrade under extreme climate conditions in northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Yunhu Shang; Xingwen Fan (Transportation Geotechnics, 2024)

A novel physics-based cloud retrieval algorithm based on neural networks (CRANN) from hyperspectral measurements in the O2-O2 band - Wenwu Wang; Husi Letu; Huazhe Shang; Jian Xu; Huanhuan Yan; Lianru Gao; Chao Yu; Jianbin Gu; Jinhua Tao; Na Xu; Lin Chen; Liangfu Chen (Remote Sensing of Environment, 2024)

Use of transdermal trazodone before veterinary visit to reduce stress and anxiety in cats - Pei-Chi Shih; Shang-Lin Wang (Journal of Veterinary Behavior, 2024)

The flow regimes of two parallel-connected chambers respectively with a mechanical extractor and a buoyancy source - Yi-Jiun Peter Lin; Shang-Qian Li (Energy and Buildings, 2024)

A micro-capillary jetting technology for liquid-liquid microdispersion with narrow size distribution - Qichen Shang; Lin Sheng; Daiwei Gu; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Observed surface heat fluxes partitioning during the local growing season over the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Danrui Sheng; Hanlin Niu; Peili Wu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Shaoying Wang; Shihua Lyu (Agricultural and Forest Meteorology, 2024)

Spatiotemporal Variability and Environmental Controls of Temperature Sensitivity of Ecosystem Respiration across the Tibetan Plateau - Danrui Sheng; Xianhong Meng; Shaoying Wang; Zhaoguo Li; Lunyu Shang; Hao Chen; Lin Zhao; Mingshan Deng; Hanlin Niu; Pengfei Xu; Xiaohu Wen (Advances in Atmospheric Sciences, 2024)

Phosphorus and selenium compounding mitigates Cr stress in peanut seedlings by enhancing growth homeostasis and antioxidant properties - Hongliang Yin; Yongping Jing; Yunqing Lin; Ningning Song; Haiying Zong; Fangli Wang; Shaojing Li; Xin Song; Hong Hou; Yuxian Shang Guan; Quanli Zong; Jun Liu (Environmental Science and Pollution Research, 2024)

Size-dependent deleterious effects of nano- and microplastics on sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Xiaofang Han; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Chunqiu Zhang; Xuejun Shang; et al. (Toxicology, 2024)

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The effects of Lactiplantibacillus plantarum 3-19 and Pediococcus pentosaceus 18-1 on preventing the accumulation of biogenic amines and promoting the production of volatile organic compounds during sour meat fermentation - Hao Shang; Ying Yue; Bingrui Guo; Chaofan Ji; Sufang Zhang; Liang Dong; Ilario Ferrocino; Luca Simone Cocolin; Xinping Lin (International Journal of Food Microbiology, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

A medium to long-term variations in hydrothermal process and deformation of high-speed railway subgrade in high-altitude cold region, Northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Yunhu Shang; Chunqing Li (Cold Regions Science and Technology, 2024)

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Metabolic engineering of Saccharomyces cerevisiae for high-level production of (+)-ambrein from glucose - Chumin Lin; Xiaopeng Zhang; Zhongju Ji; Baolian Fan; Yaman Chen; Yuhong Wu; Yuhong Gan; Zhengping Li; Yi Shang; Lixin Duan; Feng Wang (Biotechnology Letters, 2024)

Retrieval and spatiotemporal variation of total suspended matter concentration using a MODIS-derived hue angle in the coastal waters of Qinhuangdao, China - Lin Wang; Xiang Wang; Qinghui Meng; Yanlong Chen; Xinxin Wang; Lingling Jiang; Yuhao Shang (Frontiers in Marine Science, 2024)
The CIE hue angle has significant potential in marine ecology and environment monitoring using remote sensing methods. It is calculated from the remote sensing reflectance ( R rs ) of all visible bands, which serves as a comprehensive indicator of seawater radiance information and represents one of the key quantitative parameters for assessing seawater color. In this study, a remote sensing retrieval model of total suspended matter concentration (TSM) was developed using the in situ measured data acquired in the coastal waters of Qinhuangdao from 2013 to 2021. This model, based on the CIE hue angle, achieved performance metrics of R 2 = 0.68, MAPE=24.47%, and RMSE=2.72 mg/L, demonstrating better accuracy than traditional empirical models that utilize fewer bands. Based on this model, the monthly and interannual TSM in the coastal waters of Qinhuangdao from 2003 to 2023 were retrieved. Influenced by natural factors, such as the monsoons, the TSM in the coastal waters of Qinhuangdao generally exhibited a trend of first decreasing and then increasing from January to December. Except for certain anomalous years (2007, 2008, 2017, etc.), the overall variation process of TSM from 2003 to 2023 showed an initial increase followed by a decrease, closely related to the pollution reduction management requirements implemented by the Chinese government in different periods. The findings of this paper demonstrate that the coastal waters of Qinhuangdao have become clearer, and the ecological environment has been effectively improved as a result of the Chinese government’s vigorous promotion of ecological civilization construction, adhering to the development concept that ‘lucid waters and lush mountains are invaluable assets’, and by introducing the action plan for the comprehensive treatment of pollution in the Bohai Sea.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Combustion and emission characteristics of a gasoline/ammonia fueled SI engine and chemical kinetic analysis of NOx emissions - Shang Liu; Zhelong Lin; Yunliang Qi; Guoxiang Lu; Bo Wang; Li Li; Zhi Wang (Fuel, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

Sea surface temperature prediction by stacked generalization ensemble of deep learning - Hao Dai; Famei Lei; Guomei Wei; Xining Zhang; Rui Lin; Weijie Zhang; Shaoping Shang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Influence of pure sea breeze on urban heat island in Tianjin, China: A perspective from multiple meteorological observations - Mengjiao Shang; Lijuan Cao; Jianping Guo; Zihan Guo; Lin Liu; Shaobo Zhong (Atmospheric Research, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Coupling of source rock gas expulsion intensity and reservoir quality in time and space-a key to determine gas accumulation in Upper Paleozoic tight sandstones of the Mugua gas field, Ordos Basin, China - Ziyi Wang; Shuangfang Lu; Nengwu Zhou; Yancheng Liu; Liming Lin; Yaxin Shang (Marine and Petroleum Geology, 2024)

All-natural plant-based HIPE-gels simultaneously stabilizing with Quillaja saponin and soy protein isolate: Influence of environmental stresses on stability - Xiao-Wei Chen; Tian-Ge Wang; Wen-Jun Yin; Lin-Shang Zhang; Shang-De Sun (Food Hydrocolloids, 2024)

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

Improved bacterial composition and co-occurrence patterns of rhizosphere increased nutrient uptake and grain yield through cultivars mixtures in maize - Xucun Jia; Haipeng Shang; Yibo Chen; Mengjie Lin; Yuepeng Wei; Yuxia Li; Rongfa Li; Pengfei Dong; Yinglong Chen; Yongen Zhang; Qun Wang (Science of The Total Environment, 2024)

Efficient roxarsone degradation by low-dose peroxymonosulfate with the activation of recycling iron-base composite material: Critical role of electron transfer - Xiaoyu Ma; Xitao Liu; Xiao Shang; Yanwei Zhao; Zhenguo Zhang; Chunye Lin; Mengchang He; Wei Ouyang (Journal of Hazardous Materials, 2024)

Enhanced removal of roxarsone and inorganic arsenic using ball-milled heating pad waste to activate peroxymonosulfate: Critical role of non-radical pathways - Xiaoyu Ma; Xitao Liu; Yanwei Zhao; Xiao Shang; Zhenguo Zhang; Chunye Lin; Mengchang He; Wei Ouyang (Chemical Engineering Journal, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

Occurrence and risk assessment of glycidyl and 3-monochloropropanediol esters in infant formulas marketed in Taiwan - Chen Liu; Shang-Ta Wang; Choon-Hui Tan; Zih-Ee Lin; Wei-Ju Lee (Food Additives & Contaminants: Part A, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Rare DNAJC7 Variants May Play a Minor Role in Chinese Patients with ALS - Shichan Wang; Xiaoting Zheng; Qianqian Wei; Junyu Lin; Tianmi Yang; Yi Xiao; Qirui Jiang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2024)

New insights into the treatment of polycystic ovary syndrome: HKDC1 promotes the growth of ovarian granulocyte cells by regulating mitochondrial function and glycolysis - Peiwei Cong; Bing Shang; Lina Zhang; Zhaoli Wu; Yanan Wang; Jia Li; Lin Zhang (Journal of Molecular Histology, 2024)

LncRNA STAT3-AS regulates endometrial receptivity via the STAT3 signaling pathway - Yanni Jia; Wei Wang; Jiaqi Jiang; Xinyan Zhang; Haijing Li; Suhua Gong; Zuhui Li; Haokun Liu; Chunmei Shang; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2024)

Balancing law, sustainability, and the economy in China's responsible mineral resource extraction path - Donghui Liu; Zhaoyan Shang; Tongzhi Lin; Shuguang Yue (Resources Policy, 2024)

Palaeoenvironmental changes in the Late Triassic lacustrine facies of the Ordos Basin of Northwest China were driven by multistage volcanic activity: Implications for the understanding the Carnian Pluvial Event - Miruo Lin; Kelai Xi; Yingchang Cao; Xiaobing Niu; Weijiao Ma; Xiujuan Wang; Shang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Origin and geological significance of the first discovered seafloor oil seepage in the Beikang Basin, southern South China Sea - Wei Huang; Hongfei Lai; Zhifeng Wan; Wei Zhang; Miaomiao Meng; Jiujing Shang; Jinqiang Liang; Mengjie Xu; Lin Lin (Journal of Asian Earth Sciences, 2024)

A versatile AIE probe with two cross-talk-free emissions for dual detection of SO2 and viscosity and its application in food and biological imaging - Di Zhang; Min Wang; Man Li; Lin Liu; Ran Duan; Nana Xue; He Chen; Lijun Shang; Tieliang Wang; Xujin Wu; Junfeng Zhang (Food Chemistry, 2024)

Acoustoelectric materials & devices in biomedicine - Xinyue Zhang; Yihe Zhang; Jiahe Zhang; Jing Shang; Liping Lin; Qi Liu; Qi An (Chemical Engineering Journal, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Efficient degradation of chlorpyrifos and intermediate in soil by a novel microwave induced advanced oxidation process: A two-stage reaction - Xiao Shang; Xitao Liu; Xiaoyu Ma; Zhenguo Zhang; Chunye Lin; Mengchang He; Wei Ouyang (Journal of Hazardous Materials, 2024)

Rheology and 3D printing characteristics of heat-inducible pea protein-carrageenan-glycyrrhizic acid emulsions as edible inks - Qianzhu Lin; Mengshan Shang; Xiaojing Li; Shangyuan Sang; Long Chen; Jie Long; Aiquan Jiao; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

A new complex variable solution on noncircular shallow tunnelling with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Shang-shun Lin (Computers and Geotechnics, 2024)

Directional guiding of mass and charge transfer via vertically aligned graphite nanosheets for high-rate and ultralong lifespan Dual-ion batteries - Lin Shang; Bi-Yun Shi; Xianchun Liu; Tian-Tian Zhang; Hanlin Liu; Yongping Zheng; Wei-Dong Dou; Qingguang Pan; Yongbing Tang (Chemical Engineering Journal, 2024)

Identifying ARG-carrying bacteriophages in a lake replenished by reclaimed water using deep learning techniques - Donglin Wang; Jiayu Shang; Hui Lin; Jinsong Liang; Chenchen Wang; Yanni Sun; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Identification of inducible CYP3 and CYP4 genes associated with abamectin tolerance in the fat body and Malpighian tubules of Spodoptera litura - Lin Liang; Jianyi Li; Long Jin; Kunpeng Yan; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2024)

Development of nucleic acid extraction and real-time recombinase polymerase amplification (RPA) assay integrated microfluidic biosensor for multiplex detection of foodborne bacteria - Yuting Shang; Gaowa Xing; Haifeng Lin; Yucheng Sun; Shulang Chen; Jin-Ming Lin (Food Control, 2024)

Dynamic multicolor luminescent anti-counterfeiting based on spiropyran-engineered gold nanoclusters - Lin Wang; Wencheng Zhong; Wenxing Gao; Wenfeng Liu; Li Shang (Chemical Engineering Journal, 2024)

Differences in endophytic bacterial and fungal compositions in roots between red and green Amaranthus sp. - Da Yang; Xinru Lin; Xinyan Zhou; Zujian Li; Hiromi Kurokawa; Hirofumi Matsui; Toyohisa Fujita; Shang-Dong Yang (South African Journal of Botany, 2023)

Diagenesis as a control on the tight sandstone reservoir quality of the upper Carboniferous strata in the northeastern Ordos basin, China - Ziyi Wang; Shuangfang Lu; Nengwu Zhou; Yancheng Liu; Liming Lin; Yaxin Shang; Guangshun Xiao; Jun Wang (Marine and Petroleum Geology, 2023)

A study of the thermal comfort in urban mountain parks and its physical influencing factors - Yisha Liu; Yumao Lai; Lin Jiang; Bin Cheng; Xinyu Tan; Fanxi Zeng; Shuang Liang; Aoyan Xiao; Xiaowei Shang (Journal of Thermal Biology, 2023)

Deep exploration of lipid oxidation into flavor compounds: A density functional theory study on (E)-2-decenal thermal oxidative reaction - Binchen Wang; Shang Wang; Yi Wang; Sufang Zhang; Xinping Lin; Xianbing Xu; Chaofan Ji; Huipeng Liang; Liang Dong (Food Chemistry, 2023)

Aquaculture environment changes fish behavioral adaptability directly or indirectly through personality traits: a case study - Zonghang Zhang; Wuhan Lin; Dongjian He; Quanming Wu; Canrui Cai; Huaxuan Chen; Yangke Shang; Xiumei Zhang (Reviews in Fish Biology and Fisheries, 2023)

Corrosion-induced moment redistributions of RC frame structures under service loads - Chao Jiang; Deng-Feng Shang; Xiang-Lin Gu; Hong-Fei Zhang; Wei-Ping Zhang (Engineering Structures, 2023)

Packed OV-SnO2-Sb bead-electrodes for enhanced electrocatalytic oxidation of micropollutants in water - Chao Yang; Lin Lin; Shanshan Shang; Shengshou Ma; Feiyun Sun; Kaimin Shih; Xiao-yan Li (Water Research, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Supplemental irrigation at the jointing stage of late sown winter wheat for increased production and water use efficiency - Sen Wang; Yuxi Niu; Li Shang; Zhenyan Li; Xiang Lin; Dong Wang (Field Crops Research, 2023)

Numerical simulation and experimental validation of the seismic response of suspended grooved-fit piping systems - Lin Qiu; Qingxue Shang; Jichao Li; Peng Pan; Tao Wang (Engineering Structures, 2023)

Magnusiomyces Capitatus Lung Nodule in a Patient with Nasopharyngeal and Hepatocellular Carcinoma - Shih-Hao Lo; Hsin-Hui Wang; Ya-Ting Chang; Chih-Hung Lin; Po-Liang Lu; Shang-Yi Lin (Mycopathologia, 2023)

Preliminary investigation of building damage in Hatay under February 6, 2023 Turkey earthquakes - Tao Wang; Jie Chen; Yujiang Zhou; Xiaoqing Wang; Xuchuan Lin; Xiaoting Wang; Qingxue Shang (Earthquake Engineering and Engineering Vibration, 2023)

Adsorption and desorption characteristics of heavy metals onto conventional and biodegradable plastics - Wei-Hong Lin; Hsi-Yen Wang; Jeff Kuo; Shang-Lien Lo (Chemosphere, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Hydrodynamic controls on nitrogen distribution and removal in aquatic ecosystems - Lin Wang; Songhao Shang; Wenzhi Liu; Dongli She; Wei Hu; Yi Liu (Water Research, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Influence of cyclic hardening characteristic on seismic performance of welded austenitic stainless steel H-section beam-column - Yu Chen; Feng Zhou; Shuai Zheng; Jianquan Li; Chengzhi Shang; Xingxin Lin (Engineering Structures, 2023)

Light-activated extracellular matrix microcarriers with engineered MSCs loading for autoimmune psoriasis treatment - Xiang Lin; Lijun Cai; Min Nie; Xiangyi Wu; Gaofeng Liang; Luoran Shang; Yuanjin Zhao (Chemical Engineering Journal, 2023)

EIF4A3-Induced Exosomal circLRRC8A Alleviates Granulosa Cells Senescence Via the miR-125a-3p/NFE2L1 axis - Jie Xing; Mengxue Zhang; Shijie Zhao; Mingjun Lu; Li Lin; Lu Chen; Wujiang Gao; Wenxin Li; Junyu Shang; Jiamin Zhou; Xiaolan Zhu (Stem Cell Reviews and Reports, 2023)
Premature ovarian failure (POF) is an important cause of female infertility and seriously impacts the physical and psychological health of patients. Mesenchymal stromal cells-derived exosomes (MSCs-Exos) have an essential role in the treatment of reproductive disorders, particularly POF. However, the biological function and therapeutic mechanism of MSCs exosomal circRNAs in POF remain to be determined. Here, with bioinformatics analysis and functional assays, circLRRC8A was found to be downregulated in senescent granulosa cells (GCs) and acted as a crucial factor in MSCs-Exos for oxidative damage protection and anti-senescence of GCs in vitro and in vivo. Mechanistic investigations revealed that circLRRC8A served as an endogenous miR-125a-3p sponge to downregulate NFE2L1 expression. Moreover, eukaryotic initiation factor 4A3 (EIF4A3), acting as a pre-mRNA splicing factor, promoted circLRRC8A cyclization and expression by directly binding to the LRRC8A mRNA transcript. Notably, EIF4A3 silencing reduced circLRRC8A expression and attenuated the therapeutic effect of MSCs-Exos on oxidatively damaged GCs. This study demonstrates a new therapeutic pathway for cellular senescence protection against oxidative damage by delivering circLRRC8A-enriched exosomes through the circLRRC8A/miR-125a-3p/NFE2L1 axis and paves the way for the establishment of a cell-free therapeutic approach for POF. CircLRRC8A may be a promising circulating biomarker for diagnosis and prognosis and an exceptional candidate for further therapeutic exploration. Graphical Abstract

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Impact of climatic and vegetation dynamic change on runoff over the Three Rivers Source Region based on the Community Land Model - Mingshan Deng; Xianhong Meng; Yaqiong Lu; Lele Shu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Danrui Sheng; Xinmao Ao (Climate Dynamics, 2023)

HIV-1 subtype B Tat enhances NOTCH3 signaling in astrocytes to mediate oxidative stress, inflammatory response, and neuronal apoptosis - Lin Gao; Weixi Sun; Dongmei Zhang; Yanxing Shang; Li Li; Wenhua Tao; Lei Zhang; Hongbin Liu (Journal of NeuroVirology, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Boston ivy-inspired natural-rich binder with strong adhesion for advanced silicon-based anodes - Xiangyu Lin; Yong Wen; Jie Wang; Hongyi Shang; He Liu; Xu Xu (Chemical Engineering Journal, 2023)

N-doped biochar mediated peroxydisulfate activation for selective degradation of bisphenol A: The key role of potential difference-driven electron transfer mechanism - Jiaqu Tan; Xinmin Chen; Mengru Shang; Jiannan Cui; Dongya Li; Fan Yang; Zhen Zhang; Haotian Zhang; Qitang Wu; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Distribution, Source Identification, and Output flux of Barium in Surface Waters in the Sanjiangyuan Region and Qilian Mountain Region of Tibetan Plateau - Zuxiu Yao; Guangyi Sun; Li Lin; Wei Zhang; Junfang Zhang; Lingjian Gao; Lihai Shang (Bulletin of Environmental Contamination and Toxicology, 2023)

Enhancing the Thermotolerance of Isochrysis zhangjiangensis Through Co-culturing With Algoriphagus marincola - Simin Xu; Jiayi Cao; Minnan Wu; Yijun Xu; Yuanyuan Wu; Kaixi Shang; Bin Ma; Lin Zhang; Deshui Chen; Xinyu Liu; Xiaojun Yan; Jilin Xu (Marine Biotechnology, 2023)

Screening of Artificial Diet Formulations for Sugarcane Stalk Borer Chilo sacchariphagus Bojer - Ji-li Wei; Xue-hong Pan; Xian-kun Shang; Cheng-hua Huang; Yong-lin Ma (Sugar Tech, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Transcriptomic and metabolomic analyses revealed epiboly delayed mechanisms of 2,5-dichloro-1, 4-benuinone on zebrafish embryos - Yuanyao Chen; Jingming Wang; Zhiquan Yu; Lin Xiao; Jia Xu; Kai Zhao; Huiping Zhang; Xuejun Shang; Chunyan Liu (Environmental Science and Pollution Research, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

An amphiphilic macrocyclic acylhydrazone dimer: Facile synthesis and dual channel detection and removal of phthalate anion - Zhengning Shu; Shitao Sun; Ning Gu; Zhichao Yang; Yongxin Shang; Yi Yang; Mingyu Xia; Bin Lin; Peng Yang (Analytica Chimica Acta, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

The impacts of extreme marine weather and marine scientific and technological innovation on marine economic development: Evidence form China’s coastal regions - Chenggang Li; Hongye Jia; Yikang Wan; Yongxiang Hu; Bingying Zeng; Wanyue Zhang; Xiangbo Fan; Tao Lin; Guofei Shang; Weiyan Wang (Frontiers in Marine Science, 2023)
The extreme marine weather is a very vital factor and has important implications for of marine economic development. However, there is a lack of systematic and quantitative analyses of its impact on the marine economic development. Here, we study the impacts of extreme marine weather on marine economic development of 11 coastal regions in China, using the dynamic panel model. We found that extreme marine weather exerts a significant negative impact on the marine economic development. The marine scientific and technological innovation promotes marine economic development in a prominent manner. The marine scientific and technological innovation slows down the unfavorable impact of extreme marine weather on the marine economy. After considering different industries for marine economic development and heterogeneity, we found that extreme marine weather and marine scientific and technological innovation have a great impact on marine economic development in the tertiary industry and the areas with high development concerning marine economy level, while deliver a small impact on the marine economic development in the primary industry and the areas low development level. This paper empirically studies the relationship between the two variables of marine extreme weather and marine science and technology innovation and its impact on marine economic development, enriches the research perspective of extreme weather on marine economic development, and provides new method evidence for improving the level of marine scientific and technological innovation and promoting the development of marine economy.

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Adenosine A2A receptor controls the gateway of the choroid plexus - Mengqian Ye; Mengru Wang; Yijia Feng; Huiping Shang; Yuwen Yang; Lanxin Hu; Muran Wang; Serhii Vakal; Xiangxiang Lin; Jiangfan Chen; Wu Zheng (Purinergic Signalling, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Activity-density and spatial distribution of termites on a fine-scale in a tropical rainforest in Xishuangbanna, southwest China - Myo Thant; Xiaobing Lin; Anjana J. Atapattu; Min Cao; Shang-wen Xia; Shengjie Liu; Xiaodong Yang (Soil Ecology Letters, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Spatial allocation of LID practices with a water footprint approach - Wen-Kai Chuang; Zih-Ee Lin; Tzu-Chi Lin; Shang-Lien Lo; Chia-Lin Chang; Pei-Te Chiueh (Science of The Total Environment, 2023)

A framework for the sustainable risk assessment of in-river hydraulic structures: A case study of Taiwan’s Daan River - Dong-Sin Shih; Shang-Shu Shih; Shaohua Marko Hsu; Shih-Yuan Lin; Yiching Lin; Chi-Tung Hung; Kai Wang (Journal of Hydrology, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Evaluation of the mycotoxin patulin on cytotoxicity and oxidative stress in human glioblastoma cells and investigation of protective effect of the antioxidant N-acetylcysteine (NAC) - Shu-Shong Hsu; Yung-Shang Lin; Li-Min Chio; Wei-Zhe Liang (Toxicon, 2023)

Subacute Cadmium Exposure Induces Necroptosis in Swine Lung via Influencing Th1/Th2 Balance - Wenyue Zhang; Xinyue Sun; Xu Shi; Xue Qi; Shaoqian Shang; Hongjin Lin (Biological Trace Element Research, 2023)

Spatial–temporal variations and pollution risks of mercury in water and sediments of urban lakes in Guangzhou City, South China - Xiaojun Wang; Wei Zhong; Bingxiang Wang; Mingying Quan; Tianhang Li; Durui Lin; Shengtan Shang; Chan Zhu; Churan Zhang; Yiling Liao (Environmental Science and Pollution Research, 2022)

Impact of Petroleum Contamination on the Structure of Saline Soil Bacterial Communities - Ying Zhang; Xiaojie Sun; Cheng Qian; Lin Li; Xiufang Shang; Xinfeng Xiao; Yu Gao (Current Microbiology, 2022)

Application of Three-Dimensional Explicit Discontinuous Deformation Analysis on Wave Propagation in Rock Masses Using Three Viscous Boundaries with the Remedy for Artificial Joints - Xi Wang; Wei Wu; Hehua Zhu; Hong Zhang; Jeen-Shang Lin (Rock Mechanics and Rock Engineering, 2022)

Application of synthetic data to establish the working framework for multivariate statistical analysis of river pollution traceability — the heavy metals in Nankan River, Taiwan - Chun-Chun Lin; Shang-Lien Lo; Sofia Ya-Hsuan Liou (Environmental Science and Pollution Research, 2022)

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Effects of Zinc Glycinate on Growth Performance, Serum Biochemical Indexes, and Intestinal Morphology of Yellow Feather Broilers - Xiaoping Zhu; Xiuguo Shang; Guozhao Lin; Haojie Li; Xin Feng; Huihua Zhang (Biological Trace Element Research, 2022)
The purpose of this study was to investigate the effects of zinc glycinate (Gly-Zn) on growth performance, serum biochemical index, intestinal morphology, and hepatic metallothionein (MT) mRNA expression in the liver of yellow feather broilers. A total of 540 18-day-old yellow feather broilers were randomly divided into three groups: control group (basal diet), ZnSO 4 group (basal diet plus 60 mg Zn/kg from ZnSO 4 ), and Gly-Zn group (basal diet plus 60 mg Zn/kg from zinc glycinate). Each treatment group had 6 replicates with 30 birds in each replicate. The experiment lasted for 42 days (18 to 59 days of age). The results showed that Gly-Zn supplementation significantly improved the average daily gain (ADG) and average daily feed intake (ADFI) of broilers during 18 to 39 days of age compared with that in the control group ( P < 0.05) but not different from the ZnSO 4 group. The Gly-Zn group had higher glutathione peroxidase (GSH-Px) ( P < 0.05) and lower malondialdehyde (MDA) concentrations than the broilers in the control and ZnSO4 group. It was also observed that zinc content in the tibia of Gly-Zn group broilers was higher than the control and ZnSO4 group ( P < 0.05). The results of intestinal morphology parameters showed that the Gly-Zn group significantly increased the villus height in duodenum and jejunum ( P < 0.05) and decreased crypt depth in duodenum and ileum compared to the control group. However, there were no significant differences between the Gly-Zn group and ZnSO 4 group in duodenum and ileum regarding intestinal morphology parameters. The Gly-Zn group significantly increased mRNA expression of MT in the liver than both control and ZnSO 4 groups ( P < 0.05). Collectively, the results indicated that supplementing 60 mg Zn/kg through zinc glycinate improved growth performance and serum indexes as well as intestinal morphology of yellow feather broilers. It also regulates MT gene expression more effectively than the ZnSO 4 group at the transcriptional level.

Cluster analysis of the domain of microseismic event attributes for floor water inrush warning in the working face - Guo-Jun Shang; Xiao-Fei Liu; Li Li; Li-Song Zhao; Jin-Song Shen; Wei-Lin Huang (Applied Geophysics, 2022)

Vegetation dynamics and their response to Holocene climate change derived from multi-proxy records from Wangdongyang peat bog in southeast China - Lin Zhao; Chunmei Ma; Zhenming Wen; Wei Ye; Guangchun Shang; Lingyu Tang (Vegetation History and Archaeobotany, 2022)

The Impact of the Antipsychotic Medication Chlorpromazine on Cytotoxicity through Ca2+ Signaling Pathway in Glial Cell Models - Che-Sheng Chu; Yung-Shang Lin; Wei-Zhe Liang (Neurotoxicity Research, 2022)

Functional connections between bird eggshell stiffness and nest characteristics through risk of egg collision in nests - Chih‐Ming Hung; Shu‐Han Tsao; Pei‐Lin Chiang; Shang‐Ping Wu; Mao‐Ning Tuanmu; Jia‐Yang Juang (Ecology Letters, 2022)
Eggs and nests are two critical traits for the ecological success of birds. Their functional interactions, however, remain unclear. Here, we examined the functional connections between egg stiffness and nest attachment, site and structure for 1350 avian species. We revealed high eggshell stiffness for eggs in nests with a pensile attachment, located on non‐tree vegetation or having a domed shape, suggesting that birds produce stiffer eggs in response to higher egg‐collision risk in unstable or enclosed nests. Interdependence models suggested that the evolution of eggshell stiffness was more likely to be driven by than drive that of nest characters. Our results implied a trade‐off between investment in competing for established nesting niches and producing stiff eggs to explore novel niches with high collision risk, possibly mediated by predation or thermoregulation. This study highlights an overlooked connection between nests and eggshells that may have broadened the ecological niches of birds.

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Genome-wide analysis of the rose (Rosa chinensis) NAC family and characterization of RcNAC091 - Lifang Geng; Lin Su; Lufeng Fu; Shang Lin; Jianmei Zhang; Qinghua Liu; Xinqiang Jiang (Plant Molecular Biology, 2022)

Unloading Response Characteristics of Cross Fault Caverns: Effect of Fault Angles - Yong-Hui Shang; Lin-Rong Xu; Yong-Wei Li (Geotechnical and Geological Engineering, 2022)

Spatial variation and association between maternal chemical fertilizer exposure and preterm birth in a rural area in Northern China - Jiajia Li; Shiqi Lin; Jilei Wu; Yu Li; Xuejun Shang; Lijun Pei (Environmental Science and Pollution Research, 2022)

Evaluation of surface albedo over the Tibetan Plateau simulated by CMIP5 models using in‐situ measurements and MODIS - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Shaoying Wang; Lunyu Shang; Hao Chen; Shihua Lyu (International Journal of Climatology, 2022)
Surface albedo plays a key role in the energy and water cycles, and reasonable parameterizations of surface albedo will be greatly helpful to improve the simulation of radiation partition in climate models. In‐situ measurements of albedo from five sites over the Tibetan Plateau (TP) and MODIS albedo product are used to evaluate monthly, annual, and seasonal variations of the surface albedo simulated by 24 Global Climate Models (GCMs) archived by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Potential factors contributing to the bias of simulated albedo were investigated. The results show that the monthly albedo of 24 GCMs varied across models, and the difference among the models was smaller in the June–July–August period than the December–January–February period. The ensemble mean albedo of the 24 GCMs was more consistent with the in‐situ measurements than the individual model. The albedo calculated from the BNU‐ESM, GFDL‐CM3, INM‐CM4, MIROC4h, MIROC‐ESM, and MIROC‐ESM‐CHEM models coincided with the observations from June to September, increasing rapidly to above 0.4 from November. However, the annual cycle of surface albedo was insignificant when simulated by some models, such as CanESM2, CSIRO‐Mk3.6.0, CMCC‐CMS, IPSL‐CM5A‐MR, and MPI‐ESM‐MR. Additionally, the surface albedo was overestimated by CMIP5 multi‐model ensemble mean—with a smaller amplitude of daily albedo—compared with the values estimated from in‐situ observations and MCD43A3. In all 24 models, snow albedo parameterization schemes were found to variably fit the attenuation of snow albedo over time. The cold temperature, relatively more precipitation, fresh snow density, and albedo in these models led to large biases in snow depth and ablation. The surface albedo tends to increase without the influence of blowing snow and withered grass on the model's albedo.

Zeb2/Axin2-Enriched BMSC-Derived Exosomes Promote Post-Stroke Functional Recovery by Enhancing Neurogenesis and Neural Plasticity - Rui Wei; Lin Zhang; Wei Hu; Xinying Shang; Yuyan He; Wei Zhang (Journal of Molecular Neuroscience, 2022)

Technical methodologies for the assessment of the impacts of reclamation projects on marine ecology - Yurong Ouyang; Lin Wu; Juanjuan Dai; Yaojian Wu; Ling Cai; Qingsheng Li; Jianwei Wu; Shang Jiang (Environmental Science and Pollution Research, 2022)

Multifunctional biological properties and phytochemical constituents of Mangifera indica L. seed kernel extract for preventing skin aging - Worrapan Poomanee; Watcharee Khunkitti; Wantida Chaiyana; Nutjeera Intasai; Wei-Chao Lin; Shang-Chian Lue; Pimporn Leelapornpisid (Toxicological Research, 2021)

The impact of green credit policy on energy efficient utilization in China - Xiaowei Ma; Weiwei Ma; Lin Zhang; Yi Shi; Yuping Shang; Huangxin Chen (Environmental Science and Pollution Research, 2021)

Enhanced adsorption properties of organic ZnCr-LDH synthesized by soft template method for anionic dyes - Jia Lin; Yude Zhang; Qian Zhang; Jinli Shang; Fuyao Deng (Environmental Science and Pollution Research, 2021)

Effects of periodically varying codes on separation of multisource blended data - Meng-Yao Jiao; Tian-Yue Hu; Yang Liu; Zhen-Zhen Yu; Shang-Lin Liang; Li-Chao Liu; Ji-Wei (Applied Geophysics, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Does environmental engineering help rural industry development? Discussion on the impact of Taiwan’s “special act for forward-looking infrastructure” on rural industry development - Chin-Hsien Hsu; Hsiao-Hsien Lin; Shang-Wun Jhang; Tzu-Yun Lin (Environmental Science and Pollution Research, 2021)
This study investigated the impact of environmental engineering on existing venues, venues and operations management. First, the literature analysis and field survey method are used to summarize the current situation of the venue. Then, 420 questionnaires are collected for statistical verification analysis, combined with the interview method to understand the deepest feelings of the people, and finally discussed with a multi-inspection method. The researcher believes that although environmental construction can improve infrastructure and human quality of life, which, after all, are experiment after completion. If, before construction, a good communication channel; obtaining consensus from the people and businesses; acquiring precise information; spraying water to reduce dust; increasing the height of the peripheral fence; planning a substitutive plan; avoiding crowds; reducing mistakes in the process; avoiding influencing the water and electricity supply and soil, water, and environment sanitation; and planning for a substitutive route and parking space with subsidy for damages are not possible, a negative image will be produced, willingness to spend will be reduced in the people due to the blocking of the view by the building (75%), the billboard will lose its functionality (63.2%), and inconvenience will be caused by the line of movement (75%) and parking space (55.9%), which are not helpful for development.

Anti-Inflammatory Effects of an Extract from Pseudomonas aeruginosa and Its Purified Product 1-Hydroxyphenazine on RAW264.7 Cells - Jun Xiao; Aye Aye Thwe; Tingting Liu; Dafei Gong; Wanhua Lin; Changhua Shang; ZuJun Lu (Current Microbiology, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Flower biology and ontogeny of the tung tree (Vernicia fordii Hemsl.) - Wenying Li; Meilan Liu; Xiang Dong; Heping Cao; Ye Wu; Hai Shang; Huimeng Huang; Lin Zhang (Trees, 2020)

Angle-Based Contact Detection in Discontinuous Deformation Analysis - Hong Zhang; Jing-wen Zhang; Wei Wu; Xi Wang; Hehua Zhu; Jeen-shang Lin; Jian-gang Chen (Rock Mechanics and Rock Engineering, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Nitrogen‐induced acidification, not N‐nutrient, dominates suppressive N effects on arbuscular mycorrhizal fungi - Shang Pan; Yang Wang; Yunpeng Qiu; Dima Chen; Lin Zhang; Chenglong Ye; Hui Guo; Weixing Zhu; Aiqun Chen; Guohua Xu; Yi Zhang; Yongfei Bai; et al. (Global Change Biology, 2020)
Arbuscular mycorrhizal fungi (AMF) form symbiosis with most terrestrial plant roots, obtaining photosynthates in return for mineral nutrients. Ecological theories based on the economics of trading partnership predict that nutrient enrichment would suppress AMF. Experimental results from nitrogen (N) and phosphorus (P) additions, however, were highly variable, and the underlying mechanisms remain unclear. Here we show distinct AMF responses to soil N:P stoichiometry manipulations via gradients of long‐term N and P additions in a Mongolian steppe. A complementary experiment with an acid addition gradient was designed to help tease apart the effect of N‐induced acidification from N nutrient. AMF root colonization and extraradical fungal biomass progressively decreased along the P gradient under two distinct host plant species, suggesting a carbon (C)‐P tradeoff. In contrast, low to moderate N inputs increased both AMF parameters, corresponding to the increasing N:P ratio. Yet, high N inputs reduced AMF colonization and biomass, and the magnitudes of N‐led inhibition were similar to those under acid additions that induced comparable changes in soil pH. Structural equation modeling further showed that while soil N:P stoichiometry primarily controlled the effect of P addition on AMF, N‐induced soil acidity overtook the N:P stoichiometry under high N inputs and dominated the effects of reactive N on AMF. In addition, AMF community composition in roots was more dependent on host plants and unresponsive to changes in soil nutrients. We further proposed a comprehensive framework that integrates biological and geochemical effects of reactive N and P inputs on AMF. Together, these results indicate that while the C‐P tradeoff controls P suppression of AMF, N‐induced acidification dominates the N inhibition. Our findings suggest that incorporation of geochemical impacts of N and P inputs would facilitate modeling efforts to project mycorrhizal impact on plant interactions and soil C balance under future nutrient enrichment scenarios.

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

Uncertainty of volume fraction in bimrock using the scan-line method and its application in the estimation of deformability parameters - Yu-Chen Lu; Yong-Ming Tien; Charng Hsein Juang; Jeen-Shang Lin (Bulletin of Engineering Geology and the Environment, 2020)
The volume fraction within a bimrock or bimsoil is an essential parameter that is useful for estimating the engineering properties of heterogeneous geomaterials. This paper presents analytical and numerical solutions to quantify the uncertainty of volume fraction measurements in bimrock/bimsoil using a scan-line method. The analytical solutions for the mean and variance of volume fraction estimates are based on a representative volume element model. The numerical solution is obtained through simulations of scan-line measurements. This work also employs physical tests using CT scan images from artificial bimrock/bimsoil to validate these solutions. The results demonstrate that the uncertainties of the volume fraction depend on the magnitude of the volume fraction of the blocks, the diameter of the blocks, and the length of the scan line. The proposed analytical and numerical solutions are compared with existing physical experimental tests and analytical solutions. An illustrative example to demonstrate the estimation of the uncertainty of volume fraction using the scan-line measurement is present. Finally, an example application of the volume fraction characterization in the geological engineering, in terms of Young’s modulus estimation and characterization, is provided.

Microbial synthesis of functional odd-chain fatty acids: a review - Lin-Shang Zhang; Shan Liang; Min-Hua Zong; Ji-Guo Yang; Wen-Yong Lou (World Journal of Microbiology and Biotechnology, 2020)

On function-on-function regression: partial least squares approach - Ufuk Beyaztas; Han Lin Shang (Environmental and Ecological Statistics, 2020)

Predicting 3D heterogeneous in situ stress field of Gaoshangpu Oilfield northern area, Nanpu Sag, Bohai Bay Basin, China - Ke Xu; Junsheng Dai; Jianwei Feng; Bifeng Wang; Lin Shang; Lu Fang; Shuo Wang (Arabian Journal of Geosciences, 2020)

Training Future Leaders: Experience from China-ASEAN Cancer Control Training Program - Remila Rezhake; Xiao-Qian Xu; Sandrine Montigny; Anouk Berger; Shang-Ying Hu; Zhi-Hua Liu; Rengaswamy Sankaranarayanan; You-Lin Qiao; Partha Basu; Fang-Hui Zhao (Journal of Cancer Education, 2019)

Using 1-propanol to significantly enhance the production of valuable odd-chain fatty acids by Rhodococcus opacus PD630 - Lin-Shang Zhang; Pei Xu; Mei-Yun Chu; Min-Hua Zong; Ji-Guo Yang; Wen-Yong Lou (World Journal of Microbiology and Biotechnology, 2019)

Dietary tryptophan affects growth performance, digestive and absorptive enzyme activities, intestinal antioxidant capacity, and appetite and GH–IGF axis-related gene expression of hybrid catfish (Pelteobagrus vachelli♀ × Leiocassis longirostris♂) - Ye Zhao; Xiao-yun Wu; Shang-xiao Xu; Jia-yuan Xie; Kai-wen Xiang; Lin Feng; Yang Liu; Wei-dan Jiang; Pei Wu; Juan Zhao; Xiao-qiu Zhou; Jun Jiang (Fish Physiology and Biochemistry, 2019)

Feasibility of peaking carbon emissions of the power sector in China’s eight regions: decomposition, decoupling, and prediction analysis - Yong Wang; Xuelian Su; Lin Qi; Peipei Shang; Yonghong Xu (Environmental Science and Pollution Research, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

On the ecological significance of pollen color: a case study in American trout lily ( Erythronium americanum ) - Emily J. Austen; Shang‐Yao Lin; Jessica R. K. Forrest (Ecology, 2018)
Evolutionary ecologists seek to explain the processes that maintain variation within populations. In plants, petal color variation can affect pollinator visitation, environmental tolerance, and herbivore deterrence. Variation in sexual organs may similarly affect plant performance. Within‐population variation in pollen color, as occurs in the eastern North American spring ephemeral Erythronium americanum , provides an excellent opportunity to investigate the maintenance of variation in this trait. Although the red/yellow pollen‐color polymorphism of E. americanum is widely recognized, it has been poorly documented. Our goals were thus (1) to determine the geographic distribution of the color morphs and (2) to test the effects of pollen color on components of pollen performance. Data provided by citizen scientists indicated that populations range from monomorphic red, to polymorphic, to monomorphic yellow, but there was no detectable geographic pattern in morph distribution, suggesting morph occurrence cannot be explained by a broad‐scale ecological cline. In field experiments, we found no effect of pollen color on the probability of predation by the pollen‐feeding beetle Asclera ruficollis , on the ability of pollen to tolerate UV ‐B radiation, or on siring success (as measured by the fruit set of hand‐pollinated flowers). Pollinators, however, exhibited site‐specific pollen‐color preferences, suggesting they may act as agents of selection on this trait, and, depending on the constancy of their preferences, could contribute to the maintenance of variation. Collectively, our results eliminate some hypothesized ecological effects of pollen color in E. americanum , and identify effects of pollen color on pollinator attraction as a promising direction for future investigation.

Riding the Kuroshio Current: Stepping stone dispersal of the Okinawa tree lizard across the East Asian Island Arc - Shang‐Fang Yang; Shohei Komaki; Rafe M. Brown; Si‐Min Lin (Journal of Biogeography, 2018)
Aim Located hundreds of kilometres offshore of continental mainland Asia, the extremely high level of land vertebrate endemism in the East Asian Island Arc provides an excellent opportunity to test hypotheses regarding biogeographic processes and speciation. In this study, we aim to test alternative explanations for lineage diversification (vicariance versus dispersal models), and further develop a temporal framework for diversification in our focal taxon, which is consistent with the known age of these islands. We achieve these tests by investigating the historical biogeography of the Okinawa tree lizard ( Japalura polygonata ), one of the few widely‐distributed reptiles across this archipelago. Location The East Asian Island Arc: (1) Central Ryukyu (Amami and Okinawa groups); (2) Southern Ryukyu (Miyako and Yaeyama groups); (3) Taiwan and adjacent islands. Methods A total of 246 tissues were sampled from 10 localities in the Ryukyu archipelago and 17 localities in Taiwan, covering the entire distributional range of this species, including all subspecies. DNA sequences of the mitochondrial cytochrome b , 16S ribosomal RNA , nuclear BACH ‐1 and RAG ‐1 genes (total: 4,684 bp) were obtained from these samples. We used maximum likelihood and Bayesian methods to infer phylogeny and divergence time, and used a model‐fitting method of biogeographical inference to estimate ancestral range evolution. Results Multiple lines of evidence combine to identify a general pattern of dispersal‐mediated diversification northward through the archipelago, following initial dispersal from Taiwan. These included (1) a phylogenetic estimate, revealing a sequential, south‐to‐north branching pattern; (2) ancestral range estimation, inferring multiple overseas dispersals and subsequent colonization of new landmasses; and (3) a reduction in genetic variation observed in successively‐diverging lineages, decreasing from Taiwan northward, towards more remote islands. These results provide strong statistical support for an interpretation of successive bouts of dispersal via the powerful, well‐documented, south‐to‐north Kuroshio Current. Estimation of divergence times suggests that most clades in southern Ryukyu and Taiwan diverged early, giving rise to lineages that have remained isolated, and that more recently‐diverged lineages then colonized northward to subsequently occupy the landmasses of the Central Ryukyu archipelago. Main conclusions Our general inference of biogeographic history in Japalura polygonata suggested that this species originated on Taiwan and the Yaeyama group, and arrived at its current distribution in Miyako, Okinawa, Toku and Amami islands by a series of stepping‐stone dispersals, which we report for the first time for a terrestrial vertebrate endemic to this region.

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Novel non-contact control system of electric bed for medical healthcare - Chi-Chun Lo; Shang-Ho Tsai; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Nuclear Factor-kappaB-Dependent Sestrin2 Induction Mediates the Antioxidant Effects of BDNF Against Mitochondrial Inhibition in Rat Cortical Neurons - Chia-Lin Wu; Shang-Der Chen; Jiu-Haw Yin; Chi-Shin Hwang; Ding-I Yang (Molecular Neurobiology, 2016)

Efficacy of a Fructus mume Extract Combination with Stable Chlorine in Preventing Bacterial Contamination in Frozen Mackerel ( Scomber japonicus ) Fillets - Bin Zhang; Hui-min Lin; Yan Tang; Shang-gui Deng (Journal of Aquatic Food Product Technology, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Evaluation of abundant hydrocarbon-generation depressions in the deepwater area of Qiongdongnan Basin, South China Sea - Zhen Liu; Zhipeng Sun; Zisong Wang; Wei Zhang; Tingan Li; Weijun He; Fengxia Li; Shang Cao; Jingjing Liu; Lu Lin (Acta Oceanologica Sinica, 2016)

Autoinducer-2 signaling is involved in regulation of stress-related genes of Deinococcus radiodurans - Lin Lin; Tao Li; Shang Dai; Jiangliu Yu; Xiuqin Chen; Liangyan Wang; Yunguang Wang; Yuejin Hua; Bing Tian (Archives of Microbiology, 2016)

Effect of methane emission increases in East Asia on atmospheric circulation and ozone - Lin Shang; Yi Liu; Wenshou Tian; Yuli Zhang (Advances in Atmospheric Sciences, 2015)

Mitoflash altered by metabolic stress in insulin-resistant skeletal muscle - Yi Ding; Huaqiang Fang; Wei Shang; Yao Xiao; Tao Sun; Ning Hou; Lin Pan; Xueting Sun; Qi Ma; Jingsong Zhou; Xianhua Wang; Xiuqin Zhang; et al. (Journal of Molecular Medicine, 2015)

Spatial dynamics of pollination in dioecious Shepherdia canadensis (Elaeagnaceae) - Shang-Yao Lin; Erica Nol; Marcel E. Dorken (Plant Ecology, 2015)

A population study of killer viruses reveals different evolutionary histories of two closely related S accharomyces sensu stricto yeasts - Shang‐Lin Chang; Jun‐Yi Leu; Tien‐Hsien Chang (Molecular Ecology, 2015)
Microbes have evolved ways of interference competition to gain advantage over their ecological competitors. The use of secreted killer toxins by yeast cells through acquiring double‐stranded RNA viruses is one such prominent example. Although the killer behaviour has been well studied in laboratory yeast strains, our knowledge regarding how killer viruses are spread and maintained in nature and how yeast cells co‐evolve with viruses remains limited. We investigated these issues using a panel of 81 yeast populations belonging to three S accharomyces sensu stricto species isolated from diverse ecological niches and geographic locations. We found that killer strains are rare among all three species. In contrast, killer toxin resistance is widespread in S accharomyces paradoxus populations, but not in S accharomyces cerevisiae or S accharomyces eubayanus populations. Genetic analyses revealed that toxin resistance in S . paradoxus is often caused by dominant alleles that have independently evolved in different populations. Molecular typing identified one M 28 and two types of M 1 killer viruses in those killer strains. We further showed that killer viruses of the same type could lead to distinct killer phenotypes under different host backgrounds, suggesting co‐evolution between the viruses and hosts in different populations. Taken together, our data suggest that killer viruses vary in their evolutionary histories even within closely related yeast species.

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Expression of eggplant ascorbate peroxidase increases the tolerance of transgenic rice plants to flooding stress - Chih Ming Chiang; Long Fang O. Chen; Shang Wen Shih; Kuan Hung Lin (Journal of Plant Biochemistry and Biotechnology, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Mechanism-Based Pharmacokinetic/Pharmacodynamic Model for THIOMAB™ Drug Conjugates - Siddharth Sukumaran; Kapil Gadkar; Crystal Zhang; Sunil Bhakta; Luna Liu; Keyang Xu; Helga Raab; Shang-Fan Yu; Elaine Mai; Aimee Fourie-O’Donohue; Katherine R. Kozak; Saroja Ramanujan; et al. (Pharmaceutical Research, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Equatorward shift of the South Asian high in response to anthropogenic forcing - Xia Qu; Gang Huang; Kaiming Hu; Shang-Ping Xie; Yan Du; Xiao-Tong Zheng; Lin Liu (Theoretical and Applied Climatology, 2015)

The inner opercular membrane of the euryhaline teleost: a useful surrogate model for comparisons of different characteristics of ionocytes between seawater- and freshwater-acclimated medaka - Chao-Kai Kang; Shu-Yuan Yang; Shang-Tao Lin; Tsung-Han Lee (Histochemistry and Cell Biology, 2015)

Predicting 3D pose in partially overlapped X-ray images of knee prostheses using model-based Roentgen stereophotogrammetric analysis (RSA) - Chi-Pin Hsu; Shang-Chih Lin; Kao-Shang Shih; Chang-Hung Huang; Chian-Her Lee (Medical & Biological Engineering & Computing, 2014)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

The association of apolipoprotein E gene polymorphisms with cerebral palsy in Chinese infants - Yiran Xu; Honglian Wang; Yanyan Sun; Qing Shang; Mingjie Chen; Tongchuan Li; Dengna Zhu; Lin He; Changlian Zhu; Qinghe Xing (Molecular Genetics and Genomics, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Deposition rate and interaction of human-riverine from height increase and permanent function of an 1180 years weir in Southeast China - YanJun Shang; Hyeong-Dong Park; ZhiFa Yang; SiGuang Chen; DaMing Lin (Science China Earth Sciences, 2014)

Three new diterpenoids from the resin of Liquidambar formosana - Hong-Jie Shang; Dan-Yi Li; Wen-Jing Wang; Zhan-Lin Li; Hui-Ming Hua (Natural Product Research, 2014)

Genetic association study of adaptor protein complex 4 with cerebral palsy in a Han Chinese population - Honglian Wang; Yiran Xu; Mingjie Chen; Qing Shang; Yanyan Sun; Dengna Zhu; Lei Wang; Zhiheng Huang; Caiyun Ma; Tongchuan Li; Lin He; Qinghe Xing; et al. (Molecular Biology Reports, 2013)

Alkanes, compound-specific carbon isotope measures and climate variation during the last millennium from varved sediments of Lake Xiaolongwan, northeast China - Qing Sun; Manman Xie; Liming Shi; Zhuyue Zhang; Yuan Lin; Wenyu Shang; Kaijun Wang; Wei Li; Jiaqi Liu; Guoqiang Chu (Journal of Paleolimnology, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Investigation of array-derived rotation in TAIPEI 101 - Chin-Jen Lin; Wen-Gee Huang; Han-Pang Huang; Bor-Shouh Huang; Chin-Shang Ku; Chun-Chi Liu (Journal of Seismology, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Modeling and assessment of bridge structure for seismic hazard prevention - Jeng-Wen Lin; Cheng-Wu Chen; Shang-Heng Chung (Natural Hazards, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Unsteady inter-porosity flow modeling for a multiple media reservoir - Ren-Shi Nie; Ying-Feng Meng; Yong-Lu Jia; Jian-Lin Shang; Yong Wang; Jian-Guo Li (Acta Geophysica, 2012)

Simvastatin protects osteoblast against H2O2-induced oxidative damage via inhibiting the upregulation of Nox4 - Wei Huang; Wei-lin Shang; De-hao Li; Wen-wen Wu; Shu-xun Hou (Molecular and Cellular Biochemistry, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Acacetin inhibits the invasion and migration of human non-small cell lung cancer A549 cells by suppressing the p38α MAPK signaling pathway - Shang-Tao Chien; Su-Shun Lin; Cheng-Kun Wang; Yuan-Bin Lee; Kun-Shiang Chen; Yao Fong; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2011)

Comparative expression analysis of dehydrins between two barley varieties, wild barley and Tibetan hulless barley associated with different stress resistance - Jun-Bo Du; Shu Yuan; Yang-Er Chen; Xin Sun; Zhong-Wei Zhang; Fei Xu; Ming Yuan; Jing Shang; Hong-Hui Lin (Acta Physiologiae Plantarum, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

A GIS-based Decision Support System for Typhoon Emergency Response in Taiwan - Ming-Hsi Hsu; Albert S. Chen; Liang-Chun Chen; Cheng-Shang Lee; Feng-Tyan Lin; Chen-Jia Huang (Geotechnical and Geological Engineering, 2011)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Cost Considerations in Choosing Group Size for Group Testing in the Seed Potato Certification Program - Kuo-Szu Chiang; Sin-Hong Lai; Wen-Chuan Chung; Shang-Hu Lin; Tso-Chi Yang (American Journal of Potato Research, 2010)

Use of a GIS-based hybrid artificial neural network to prioritize the order of pipe replacement in a water distribution network - Cheng-I Ho; Min-Der Lin; Shang-Lien Lo (Environmental Monitoring and Assessment, 2010)

Metal Concentrations in Sediments of the Tamsui River, Flows Through Central Metropolitan Taipei - Dong-Shang Lai; Jye-Bin Lin; Wen-Shan Liu; Lung-Kwang Pan; Kuang-Hua Chu; Chien-Yi Chen; Ding-Bang Lin (Bulletin of Environmental Contamination and Toxicology, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Heterothallism in Saccharomyces cerevisiae isolates from nature: effect of HO locus on the mode of reproduction - TAL KATZ EZOV; SHANG-LIN CHANG; ZE’EV FRENKEL; AYELLET V. SEGRÈ; MORAN BAHALUL; ANDREW W. MURRAY; JUN-YI LEU; ABRAHAM KOROL; YECHEZKEL KASHI (Molecular Ecology, 2010)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Complete nucleotide sequence of a Chinese serotype Asia1 vaccine strain of foot-and-mouth disease virus - Junzheng Du; Huiyun Chang; Guozheng Cong; Junjun Shao; Tong Lin; Youjun Shang; Zaixin Liu; Xiangtao Liu; Xuepeng Cai; Qingge Xie (Virus Genes, 2007)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Phosphorus Load Reduction Goals for Feitsui Reservoir Watershed, Taiwan - Wen-Shang Chou; Tsu-Chuan Lee; Jen-Yang Lin; Shaw L. Yu (Environmental Monitoring and Assessment, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

Hairy Root Cultures of Gynostemma pentaphyllum (Thunb.) Makino: A Promising Approach for the Production of Gypenosides as an Alternative of Ginseng Saponins - Chen-Kai Chang; Ku-Shang Chang; Yi-Chen Lin; Sin-Yie Liu; Chien-Yuan Chen (Biotechnology Letters, 2005)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Isolation and characterization of a cellulolytic Geobacillus thermoleovorans T4 strain from sugar refinery wastewater - Shang-Kai Tai; Hsiu-Ping Pearl Lin; Jimmy Kuo; Jong-Kang Liu (Extremophiles, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

Isolation and identification of a gene in response to rice blast disease in rice - Xianwu Zheng; Xuewei Chen; Xiaohong Zhang; Zhongzhuan Lin; Junjun Shang; Jichen Xu; Wenxue Zhai; Lihuang Zhu (Plant Molecular Biology, 2004)

Cloning and expression of the α-amylase gene and oxytetracycline production in Streptomyces rimosus - Chun-Wen Cheng; Jin-Seng Lin; Yu-Tien Liu; Shang-Shyng Yang (World Journal of Microbiology and Biotechnology, 2000)

Cloning of Two New cry Genes from Bacillus thuringiensis subsp. wuhanensis Strain - White-Shang Kuo; Jong-Huon Lin; Ching-Chou Tzeng; Shui-Shang Kao; Kin-Fu Chak (Current Microbiology, 2000)

Identification of two chilling-regulated 1-aminocyclopropane- 1-carboxylate synthase genes from citrus (Citrus sinensis Osbeck) fruit - Wai Shing Wong; Wen Ning; Pei Lin Xu; Shain Dow Kung; Shang Fa Yang; Ning Li (Plant Molecular Biology, 1999)